2018
DOI: 10.24259/fs.v2i2.5356
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the special section: Agrarian transformation in Thailand - Commodities, landscapes, and livelihoods

Abstract: This is an introduction and review for a special section on agrarian transformation in Thailand. The article seeks to guide greater attention toward issues affecting rural Thai landscapes and livelihoods. Through the examination of specific commodities across various geographies, the paper seeks to refocus research towards decision making processes among rural communities. The research draws on field study cases that follow various aspects of particular commodities, including rubber, pomelo, tomato, cassava, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…2). As in other areas of Northeast Thailand, rural livelihoods in Ban Chai are in transition from small-scale rice farming to the more diversified, market-oriented production of cash crops (Rambo 2017;Choenkwan and Fisher 2018). Driven by market developments and policies, the sub-district of Ban Chai has experienced a sharp increase in sugarcane plantations at the expense of rice farming, grazing and forest land.…”
Section: Site Descriptionmentioning
confidence: 99%
“…2). As in other areas of Northeast Thailand, rural livelihoods in Ban Chai are in transition from small-scale rice farming to the more diversified, market-oriented production of cash crops (Rambo 2017;Choenkwan and Fisher 2018). Driven by market developments and policies, the sub-district of Ban Chai has experienced a sharp increase in sugarcane plantations at the expense of rice farming, grazing and forest land.…”
Section: Site Descriptionmentioning
confidence: 99%
“…However, administrative and territorial reforms have a direct impact on the development of the Agrarian sector (Mykhailova et al, 2018). Farmers certainly ensure the availability of land to work on.Recent research on several key dimensions of Agrarian transformation also alludes to demographic problems and changes in the population structure of society (Choenkwan & Fisher, 2018;Watanabe, 2017). The distribution of land ownership is one of the important factors of agricultural productivity and economic well-being of farmers and also affects their social and political status in the community (Naseer, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the negative aspects inherent in tobacco agricultural livelihoods (Choenkwan & Fisher, 2018;Leppan et al, 2014), including the heavy use of chemical inputs and direct exposure to poisonous substances in tobacco crops. Our study revealed the tobacco agricultural practices under the oversight of TTM are well aware of inappropriate chemical use in tobacco farmers.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Evidence from research carried out in developing countries shows that tobacco agriculture encompasses negative livelihood outcomes for farmers (Appau et al, 2019;Choenkwan & Fisher, 2018;Drope et al, 2004;MacKenzie et al, 2017). Lecours (2014) noted that tobacco farmers in many developing countries struggle with low net gains, high levels of indebtedness and a heavy burden from hazardous work.…”
Section: Introductionmentioning
confidence: 99%